Prospek dan Outcome Pendidikan Dayah Salafiyah di Aceh - Masrizal, Masrizal (Al-Fikrah, 2021)
This study aims to explain the prospects and outcomes of Salafiyah dayah education in Aceh. The results of this study indicate that the educational system of Dayah MUDI Mesjid Raya Samalanga has a concrete and comprehensive learning system, allowing students to be more active both in curricular and extracurricular activities. The main development forms in the prospect of the educational system of Dayah MUDI Mesjid Raya Samalanga include a series of innovations such as establishing higher education institutions within the dayah, providing equivalency classes, establishing Ma'had Aly, and reconfiguring the Salafiyah dayah curriculum, along with changes in teaching methods. The outcomes of the education at Dayah MUDI Mesjid Raya Samalanga include many alumni being active in various fields, both in academia and non-academia. In academia, alumni have become legislative members such as DPR, DPRK, and DPRA, as well as lecturers in various universities. In non-academic fields, alumni have established dayah institutions, majlis ta'lim, and become community leaders. This indicates that dayah alumni have characteristics that enable them to achieve these goals.